MOLECULAR CHARACTERIZATION OF ROTAVIRUS STRAINS OBTAINED FROM HUMAN DIARRHEIC SAMPLES AND THEIR EPIDEMIOLOGICAL IMPLICATIONS - Bermeo, Liliana; Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
An analysis of RNA electropherotypes was carried out on rotavirus isolates from diarrheic samples. Of the 328 samples analyzed, 56 were positive forrotaviral RNA and these could be classified into four different electropherotypes, according to the electrophoretic mobilities of their various RNA segments. The differences among the various electrophoretic patterns were basically due to changes in the mobilities of the genomic segments 7, 8 and 9 which make up group III. However, all electropherotypes were compatible with the pattems considered to be characteristic for group A rotavirus, and were likewise classified as short pattems. The findings suggest a moderate genetic variation among the rotavirus strains affecting the infant population studied.